2010
DOI: 10.1007/s10552-010-9603-9
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index, agricultural pesticide use, and cancer incidence in the Agricultural Health Study cohort

Abstract: Obesity is associated with increased risks of several cancers including, colon, lower esophagus, kidney, female breast, and endometrium. Some studies have associated pesticides with higher risks of cancer in agricultural populations. The interaction between obesity and pesticide use on cancer risk has not been well studied. Using data from the Agricultural Health Study we examined the association between body mass index (BMI) and the risk of cancer at 17 sites, and the interaction between BMI and pesticide use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 63 publications
2
52
0
1
Order By: Relevance
“…Cross-sectional [24,26,27,63] and longitudinal [23,25] studies have reported similar findings. This observation in our population is of great concern and a potential driver for obesity in this population due to the high exposure to pesticides.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Cross-sectional [24,26,27,63] and longitudinal [23,25] studies have reported similar findings. This observation in our population is of great concern and a potential driver for obesity in this population due to the high exposure to pesticides.…”
Section: Discussionmentioning
confidence: 68%
“…Pesticides contain chemical compounds that are widely considered as obesogenic and endocrine disruptors. These compounds are reported to modulate lipid metabolism, hormone and neurotransmitter levels and adipogenesis and thus cause weight gain [2327,63]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdominal obesity may be more strongly associated with insulin resistance than peripheral obesity (4), but there have been relatively few studies of waist circumference and waist-to-hip ratio as measures of abdominal fatness in relation to pancreatic cancer risk. A number of additional large cohort studies have been published since the WCRF/AICR report from 2007 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), thus, we conducted an updated meta-analysis of BMI, waist circumference and waist-to-hip ratio and pancreatic cancer risk with the aim to clarify whether body fatness is associated with pancreatic cancer in both men and women and in European and Asian populations as well. In addition, we wanted to clarify the dose-response relationship between BMI, waist circumference and waist-to-hip ratio and pancreatic cancer risk by conducting nonlinear dose-response analyses and by restricting the analysis to studies among non smokers or never smokers.…”
Section: Introductionmentioning
confidence: 99%
“…2), where study-specific risk estimates and their CIs are plotted, also indicates a heterogeneous set of studies. In particular, heterogeneity could be attributed to six cohort [2][3][4][5][6][7] and five case-control [8][9][10][11][12] studies. It would have been informative to identify which aspects of the individual studies contributed to heterogeneity.…”
Section: Heterogeneitymentioning
confidence: 99%